Kiai Masykur’s teaching of Sambelun (1860-1960) as a model of sufistic da’wah - Hajam Hajam; Theguh Saumantri; Gumilar Irfanullah; Indah Dwi Nurhidayah (Jurnal Ilmu Dakwah, 2022)
Purpose - literature of Sufism in the archipelago showed that  Islamic doctrines that have been preached in society have been dialectic with local developments and culture. This assumes an unique yet effective form of da’wah.  The purpose of this study is to explain the core teachings of Sambelun as a model of da’wah used by Kiai Masykur to spead Islamic teachings and doctrines among his surroundings.Method - This paper is  based on library research related to the points of Sambelun's teachings. In dissecting and uncovering Sambelun's teachings, three stages of data collection techniques are used, namely the orientation stage, the data collection stage and data analysis.Result - Sambelun teachings presuppose a human journey that must be forged and trained strictly and continuously with mujahadah and riyadhah in order to obtain the status of insan kamil  (perfect/universal man).Implication - Sambelun teachings are  combination of Sufism and local culture which made a distingtion of Javanese Islam, including in Cirebon. Sambelun introduces the essence of man which is the ultimate goal for every salik of God’s path.Originality - This research is a study of local Sufism in Cirebon by exploring the core of the character's thinking. Furthermore, this study aims to take a deeper look at the role of da’wah of  kiai masykur in speading Islam among his surroundings.  ***Tujuan - literatur tasawuf di nusantara menunjukkan bahwa ajaran Islam yang diwartakan di masyarakat telah berdialektika dengan perkembangan dan kebudayaan setempat. Ini mengasumsikan bentuk da’wah yang unik namun efektif. Tujuan dari penelitian ini adalah untuk menjelaskan inti ajaran Sambelun sebagai model da’wah yang digunakan Kiai Masykur untuk menyebarkan ajaran dan doktrin Islam di lingkungannya.Metode - Tulisan ini berdasarkan studi kepustakaan terkait dengan pokok-pokok ajaran Sambelun. Dalam membedah dan mengungkap ajaran Sambelun digunakan tiga tahapan teknik pengumpulan data yaitu tahap orientasi, tahap pengumpulan data dan analisis data.Hasil - Ajaran Sambelun mengandaikan perjalanan manusia yang harus ditempa dan dilatih secara ketat dan berkesinambungan dengan mujahadah dan riyadhah untuk memperoleh status insan kamil (manusia sempurna/universal).Implikasi - Ajaran Sambelun merupakan perpaduan tasawuf dan budaya lokal yang menjadi pembeda Islam Jawa, termasuk di Cirebon. Sambelun memperkenalkan hakikat manusia yang merupakan tujuan akhir dari setiap salik jalan Tuhan.Orisinalitas - Penelitian ini merupakan kajian tasawuf lokal di Cirebon dengan menggali inti pemikiran tokoh. Selanjutnya, penelitian ini bertujuan untuk melihat lebih dalam peran da’wah kiai masykur dalam da’wah Islam di lingkungannya.